The Sound Changes in the Minangkabau Language Spoken by Padang’s Ethnic Chinese - M. Wahyudi; Radia Fitri; Fahmi Achta Pratama; Romi Febrianto (Yayasan Keluarga Guru Mandiri, 2024)
Variations in Minangkabaunese sounds include the segmental phonemes of the Minangkabaunese spoken by the Chinese ethnic in Padang. This study aims to identify the types and rules of Minangkabaunese sound changes uttered by the Chinese. This used a qualitative descriptive approach. The data on the Minangkabaunese words spoken by the Chinese in Padang were obtained through participant observation and interviews addressing oral characteristics. The Minangkabaunese Swadesh list, recording equipment, and writing implements were used in this study. The findings show that the segmental phonemes of the Minangkabaunese voiced by ethnic Chinese in Padang deviate from standard Minangkabaunese. They use 18 out of 20 standard consonants, resulting in a disparity. The consonants /w/ and /z/ are nearly never used in standard Minangkabau. This study reveals that numerous elements, such as phonetic and phonological characteristics, affect the variations of the Minangkabaunese spoken by the Chinese in Padang. This study contributes to the advancement of linguistic theory, specifically language phonology. The findings of this study can be utilized to document the phonological system of the Minangkabaunese spoken by Chinese in Padang, which implicates the acceptance of Chinese ethnicity and diversity in Muslim-dominant Minangkabau regions. The finding shows that the MInangkabaunese language is an open system reflecting the culture of tolerance and respect for diversity.